Association of household food security status and nutritional status among preshool children in Occidental Mindoro - Dela Luna, Kim Leonard G.
Food security is defined as the state of the population having reliable access to a sufficient quantity of affordable and nutritious food. Food security concept must include both physical and economic access to food that meets people?s dietary needs as well as their food preferences. Food security is characterized by the following domain: food availability, accessibility, utilization and stability. In the Philippines, there is still no undertaking that explore the association of food security to the development of young Filipinos during their formative years. The aim of this study was to determine if household food security was associated with the nutritional status among preschool children in Occidental Mindoro. Specifically, to estimate the prevalence of the following factors among preschool children in Occidental Mindoro: household food security, undernutrition (weight-for-age and height-for-age). This was a cross-sectional study design that included 480 children, from two communities (urban and rural) of Occidental Mindoro. The sample size was determined through the use of Open Epi software with twenty per cent allocation to attrition and loss to follow-up. Three level multi-stage stratified simple random sampling was utilized by the researcher during sample selection. The researcher utilized questionnaire that included three components. Descriptive statistics were presented through the use of tables and figures. Multiple Logistic Regression Analysis was used by the researcher to determine association between household food security and nutritional status of preschool children while controlling for the confounding variables. Result of this study revealed that the prevalence of food insecurity in the province was 51.04% (95% CI: 46.55, 55.53), prevalence of low dietary diversity score was31.67% (95% CI: 27.49, 35.84), prevalence of stunting was 36.04% (95% CI: 31.73, 40.35) and prevalence of underweight was 30.24% (95% CI: 26.29, 34.55). There was a significant difference between the prevalence of food insecurity (p=0.0224) and low dietary diversity score (p=0.0107) between rural and urban communities in Occidental Mindoro. Moreover, rural barangays had higher prevalence of food insecurity and low dietary diversity score compared to urban barangays. However, research findings showed that there was no enough evidence to prove that there was a significant difference between the prevalence of stunting (p=0.3992) and underweight (p>0.999) among preschool children between the two communities. Moreover, the findings of this study showed after controlling the confounding effect of low dietary diversity score it was found that the odds of having underweight child were 7 times higher among food insecure households (OR: 7.06, 95%CI: 4.21, 11.84). Meanwhile, after controlling the confounding effect of household income and low dietary diversity score it was found that the odds of having a stunted child were 23 times higher among food insecure households (OR: 23.00, 95%CI: 12.05, 43.91). Magnitude of household food insecurity, low dietary diversity score, underweight and wasting was found to be very high in study areas, although lower compared to the national estimates; it remains of public health significance. Based from the result of this study, government must take into consideration the odds effect of household food insecurity to nutritional status of preschool children to formulate some policies advocating and targeting the effect of food insecurity.